The Analysis of Relationship Between Organizational Capacity for Change and Strategic Thinking - Gholamreza Tavakoli; Majid Ramezan; Abbas Moayya (مطالعات مدیریت بهبود و تحول, 2015)
In today’s era Organizational Capacity for Change (OCC) is an important and strategic capability and a source of competitive advantage for organizations; therefore the strategic thinkers should go beyond the daily managerial processes and crises to focus on developing the capacity for effective response to the environmental uncertainty. In this study 29 governmental organizations were surveyed. The level of Strategic Thinking and OCC in each organization was evaluated and the relationship between these two concepts was investigated by correlation test. In this research Liedtka’s model of Strategic Thinking and Judge’s model of Organizational Capacity for Change have been used. The results showed that organizations with higher level of Strategic Thinking have greater Capacity for Change. Furthermore, it was determined that there are positive and meaningful correlations between each element of Strategic Thinking (systems perspective, intent-focused, intelligent opportunism, thinking in time and hypothesis-driven) and OCC. The statistical analyses also demonstrate that there are positive and meaningful correlations between Strategic Thinking and both human capital and social infrastructure attributes of OCC.